4-Phenyl Butyric Acid (4-PBA) suppresses neutrophil recruitment in a murine model of acute rerinatal inflammation - Gille, Christian; Jungwirth, Maylis; Pezer, Silvia; Dietz-Ziegler, Stefanie; Köstlin-Gille, Natascha; Lajqi, Trim (Journal of immunology research, 2025)
Neutrophils are the first immune cells to be recruited to the site of infection and deregulated activation is linked to adverse outcome, especially in premature neonates. Dampening neutrophil activity may therefore be a means of preventing acute and chronic inflammatory diseases; however, little is known about potential drugs to modulate neutrophil activity. 4-Phenyl butyric acid (4-PBA) is a clinically used drug, which acts as a chemical chaperone to inhibit endoplasmic reticulum (ER) stress and to suppress immune activation. Here, we investigated the potential of 4-PBA to regulate neutrophil-mediated inflammation and specifically the recruitment cascade of neutrophils. We found that 4-PBA suppressed perinatal neutrophil recruitment cascade as assessed by fetal intravital microscopy (IVM), as well as transmigration of neutrophils through the endothelial compartment via the inositol-requiring enzyme (IRE)-1α/extracellular signal-regulated kinase (ERK) 1/2 signaling pathway. Likewise, 4-PBA promoted an anti-inflammatory phenotype by suppressing the release of pro-inflammatory mediators in bone marrow neutrophils and endothelial cells in vitro. Taken together, our data indicate that 4-PBA can exert anti-inflammatory effects by limiting excessive neutrophil infiltration into inflamed tissues, thereby holding significant therapeutic potential in managing various inflammatory diseases.
Gesehen am 10.11.2025